2022
DOI: 10.1039/d2ma00143h
|View full text |Cite
|
Sign up to set email alerts
|

A study of contemporary progress relating to COF materials for CO2capture and fixation reactions

Abstract: Global warming is a great threat to the very survival of our planet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 151 publications
0
18
0
Order By: Relevance
“…The capture of dialysis waste products is another use. The material combines a bispyridinium salt (BDB) with an azacalix [ 4 ] arene (ACA) following the Zincke reaction under irradiation of microwave materials at 90 °C for 3 h to generate the cationic ACA-COF [ 57 ]. Another ACA-COF was synthesized in solvothermal conditions, and the crystallinity observed was higher using microwave irradiation.…”
Section: Microwave-assisted Synthesis Of Cofsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capture of dialysis waste products is another use. The material combines a bispyridinium salt (BDB) with an azacalix [ 4 ] arene (ACA) following the Zincke reaction under irradiation of microwave materials at 90 °C for 3 h to generate the cationic ACA-COF [ 57 ]. Another ACA-COF was synthesized in solvothermal conditions, and the crystallinity observed was higher using microwave irradiation.…”
Section: Microwave-assisted Synthesis Of Cofsmentioning
confidence: 99%
“…Several applications for COFs have been explored, including molecular separations [ 2 ], removal of toxic compounds [ 3 ], gas capture [ 4 ], enzyme immobilization [ 5 ], optoelectronic applications [ 6 ], analytical chemistry [ 7 ], photocatalysis [ 8 , 9 ], electrocatalysis [ 10 ], electrochemical sensors [ 11 ], batteries [ 12 ], and solar fuel production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Many governments have established policies to mitigate CO 2 emissions in the medium to long-term plan, including carbon capture and storage (CCS). [6][7][8][9] Porous adsorbent-based separation technology offers a wellperforming and energy-efficient solution for carbon capture. [10][11][12] In the past 20 years, new families of porous adsorbents, such as metal-organic frameworks (MOFs) [13][14][15][16] and covalent organic frameworks (COFs), [17][18][19][20] have attracted signicant attention and they exhibit impressive CO 2 capture capability.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [ 36 ] reviewed the COFs from the design and synthesis to the functions. Islam et al [ 47 ] reported a study of contemporary progress relating to COF materials for CO 2 capture and fixation reactions. Recently, Zhang et al [ 48 ] focused on the design and application of ionic COFs.…”
Section: Introductionmentioning
confidence: 99%